Developing sosiocultural base thematic-integrative learning instrument for elementary school students - Slamet Arifin (Jurnal Prima Edukasia, 2017)
This study aimed at: (1) generating sociocultural base-thematic-integrative learning instrument on the theme “My Aspiration” for the students of SD N Pujokusuman 1; and (2) identifying the effectiveness of the sociocultural base-thematic-integrative learning instrument on the theme “My Aspiration”. This study referred to the steps that had been developed by Borg Gall. The developmental design was categorized into three procedures which consisted of: (a) preliminary stage; (b) development stage; and (c) testing stage. The subjects of the main experiment were 28 elementary school students. Then, the subjects of the operational test were 84 students from SDN Pujokusuman 1. The subjects of operational product test in the experimental group were 56 students and in the control group were 28 students. In gathering the data for this study, the researcher employed interview guideline, learning instrument product assessment sheet, teacher’s checklist observation sheet, student’s checklist observation sheet, learning results test, and teacher’s response questionnaire. In conducting the data analysis, the researcher made use of independent sample t-test with the rate of significance 0.05. The results of the study show that the learning instrument belongs to the “Good” category. The implementation of the learning instrument, in general, belongs to the “Very Good” category. However, there are differences between the control group and the experimental group after the implementation of the sociocultural based-thematic-integrative learning instrument with p 0.05. There is also a significant improvement with p = 0.0001.